Theorizing Democracy as a Quality, Reality, and Ideologeme - van der Zweerde, Evert (Stasis, 2017)
In today’s world “democracy” and “democratic legitimacy” are normatively dominant, making even the harshest dictators refer to “the will of the people.” At the same time, dissatisfaction with “real existing democracy” is widespread and increasing, particularly in long-standing democratic societies. If we understand democracy, primarily, as a possible quality of practices and procedures, rather than as a regime or a type of government, we can address such issues. Understanding democracy as a quality, consisting in those being affected by decisions having a “say” in those decisions, clarifies the ongoing struggle to actually have that say (which explains both the Tea Party and Nuit debout). It explains how the—inevitable—institutionalization of democratic practices and particularly their reduction to elections leads to a gap that either invites democratic innovation, or is bridged ideologically with key ideologemes like “the People” or “popular sovereignty”—an ideology which is not in contradiction with reality, but makes existing democratic realities more democratic than they actually are.